A razão neutrófilos-linfócitos e as concentrações da proteína C-reativa não são associados à força, massa muscular e capacidade funcional de pacientes transplantados renais - Santos, Heitor Oliveira (2021)
Introduction: Little is known about the association of neutrophil-lymphocyte ratio (NLR) and C-reactive protein (CRP) with the components of sarcopenia in kidney transplant patients (KTPs). Objective: This study aimed to associate NLR and CRP with strength, muscle mass, and functional capacity in KTPs. Material and methods: A cross-sectional study (n = 108) was performed. Functional capacity was assessed by the 4-meter gait speed test and short physical performance battery (SPPB), strength was evaluated by handgrip strength and five-times-sit-to-stand test (5STS), appendicular skeletal muscle mass (ASM) was estimated by bioelectrical impedance, and ASM index (ASMI) was calculated using the ASM (kg)/height (m2). Electrochemiluminescence method was used for analyzing CRP levels and cytometric method XN-3000 Sysmex for obtaining leukogram values to calculate the NLR. Results: No significant associations, both for the NLR and CRP classifications, were noted in the simple and multivariate linear regression for the sarcopenia components. Likewise, in the multivariate linear regression model adjusted for age, sex, waist circumference, total protein intake, glomerular filtration rate, use of calcineurin and mTOR inhibitors, transplant time, and energy intake, NLR and CRP levels were not associated with handgrip strength (β-values = 0.231 and 0.291, p-values = 0.389 and 0.577 for NLR and CRP classifications, respectively), 5STS (β-values = -0.114 and -0.202, p-values = 0.288 and 0.334 for NLR and CRP classifications, respectively), and ASM (β-values = -0.027 and 0.062, p-values = 0.813 and 0.788 for NLR and CRP classifications, respectively). Conclusion: NLR and CRP levels were not associated with the components of sarcopenia in KTPs.